PENGARUH TINGKAT PARTISIPASI PEREMPUAN TERHADAP KEBERHASILAN KELOMPOK USAHA BERSAMA (KUBE) DI KECAMATAN SERI KUALA LOBAM KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Nursyahira "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the district of Kuala Lobam Seri Bintan District Riau Islands Province. This study aims to determine how to influence women's participation to the success of business groups (KUBE) and to find out what are the factors that support and hinder the success of the joint venture group (KUBE). This study, entitled 'Effect of Participation of Women Against Success Business Group (KUBE) In Sub Seri Bintan Regency Kuala Lobam Riau Islands province' '. The underlying question in this research is how the influence of women's participation to the success of business groups (KUBE) and what are the factors that support and hinder the success of the joint venture group (KUBE). Making the population used in this study is the census technique. Total population of the entire members of business groups that numbered 100 members predetermined criteria. The method used is quantitative method with descriptive approach. Data filtering instrument used is observation, documentation and interview. The results have generally been carried out by the researcher, the researcher can say that there is a strong influence of women's participation to the success of business groups (KUBE) evidenced by hypothesis testing using Chi Square. Factors that support the success of the joint venture group is a factor of the level of education, experience, visit the companion and understanding of the business groups, while the factors inhibiting the success of business groups, namely the organization and working poor. Keywords: Participation, Business, Group